Ameliorative Effects of Borreria Verticillata Aqueous Extract on Adenium obesum Stem Bark Extract-Induced Histopathological Response of The Gill, Intestine, Liver, and Kidney in Clarias gariepinus (Burchell 1822) Juveniles - Muyiwa, Benedict Olurotimi; Sambo, Sohnap James; Ajadi, Abdullateef Abiodun; Adekunle, Usman Abdulrauf (Media Kedokteran Hewan, 2025)
The study was carried out to determine the effect of Borreria verticillata aqueous extract on Adenium obesum stem bark aqueous extract induced histopathological responses in the gill, intestine, liver, and kidney of Clarias gariepinus juveniles. The study consisted of ten (10) groups of fifteen (15) fish each. Groups II - V received 25, 50, 100, and 200 mg/L of the BVAE, respectively. Group VI received 0.838 mg/L of AOAE only (10% of LC50), while groups VII - X received the combinations of the extracts (GII + GVI, GIII + GVI, GIV+GVI, and GV + GVI, respectively). The histopathology observed in Group VI included complete fusion of secondary lamellae and congested blood vessels, hepatic congestion, periportal inflammation, vacuolation, and hyperplasia of bile canaliculi, hypertrophy of the muscular layer and lamina propria and hyperplasia of the goblet cells, congestion of renal blood vessels, tubular degeneration, and swollen glomeruli. The histopathology induced by exposure in GVI in the gills, liver, and kidneys were ameliorated by the administration of Borreria verticillata extract in Clarias gariepinus juveniles in terms of severity which is more in the gill where there is complete club shaped gill in exposed fish compared to the Borreria verticillata extract treated groups.